A national sports institute as a learning culture. (2nd January 2016) - Lee, Jessica; Price, Nathan
Abstract : Background and purpose : The aim of this study was to describe the learning culture for elite athletes who resided at the Australian Institute of Sport (AIS) from the perspective of the athletes themselves. As a government entity, the AIS is highly regulated by policies and strategies concerning allocation of funding, facilities, services, and resources. There is a substantial body of research examining government interest in elite sport and, in particular, national and state sporting institutes. These meso-level interactions within the AIS context no doubt have an impact on athlete learning. Learning in this context is political and economic as well as social. Thus, the cultural theory of learning is an important tool in considering the political agenda as an integral part of the learning process within the context of the AIS. Data collection and analysis : Participants for this study were purposefully selected from a larger project involving AIS scholarship holding athletes who were residents at the AIS. The final sample of six female athletes from four different sports participated in a single semi-structured interview aimed at gathering a holistic perspective of the current life experiences of the athletes. Thematic analysis involved the three steps of (1) initial coding of text in relation to the research questions, (2) the development of descriptive themes, and (3) the generation of analytical themes. The theoretical lens of the cultural theory of learning shaped the third step of the analysis. As such, the context within which practice took place including the language, social space and hierarchies, and symbolic message systems were foregrounded. Findings : The successful habitus in this field is one which was described by the athletes as organised with a plan, busy, and with multiple interests. Enhanced athletic performance and motivation to train were tied to being able to have time away from sport to relax and do other things. Being in residence at the AIS produced a commodity-driven orientation and encouraged athletes to diversify in order to increase performance, to gain further funding, to maintain their positions at the AIS which afforded the optimum balance for performance, forming a cycle of the interaction between habitus and field. Conclusion : What this investigation offers is an insight into how a set of meso- and macro-level structures around finance and performance are experienced by a sample of national sport institute residential athletes and may demonstrate conditions related to athlete satisfaction. For this group of athletes at least, 'living sport' was not conducive to maintaining elite performance and their place at the AIS. These findings are of relevance to coaches of young high-performance athletes and those involved in policy-making and athlete learning in sports institutes.